NUMERICAL ANALYSIS OF A TURBULENT PLUNGING WATER JET - Can, Omer F.; Bagatur, Tamer; Celik, Nevin (Begell House Inc, 2024)
In the present study, we employed multiphase computational fluid dynamics analysis to investigate the mechanisms of air entrainment by plunging liquid jets. The ANSY-CFX commercial software program, which is based on finiteelement analysis, was used in the numerical simulations. The effects of the exit velocity of the jet on the velocity distribution in the pool, bubble depth, and volumetric fraction of air were the extracted results of the simulations. In this article, we conducted verification analyses to compare the results obtained from our numerical runs to the results of a previously published experimental study. Good agreement was achieved between the numerical simulations and the experimental study.
Keywords: air entrainment; computational multiphase fluid dynamics; plunging water jet